The digital de-influencing wave: redefining trust in online communities - Khalil, Tayyiba; Mahmood, Chaudhry Kashif; Singh, Harcharanjit; Aftab, Faisal; Khan, Hina; Manzoor, Imran; Abdulhayee, Kashif Ahmed (Frontiers in Communication, 2025)
This research investigates the emerging role of social media de-influencers and their perceived credibility and authenticity, with a particular focus on their impact on consumer behavior. Utilizing thematic analysis, the research identifies key factors that shape de-influencer credibility, including truthful endorsements, consistent visibility, demonstrated expertise, active engagement, unique perspectives, and sincere communication. Focus group discussions with 59 participants from Pakistan revealed that de-influencers advocate for mindful consumption and ethical practices, offering a counter-narrative to the consumerist culture often promoted by traditional influencers. Grounded in Source Credibility Theory, the findings emphasize the importance of trustworthiness and expertise in building de-influencers’ authenticity. The thematic analysis provided a comprehensive understanding of participant perspectives, uncovering nuanced insights into how users critically evaluate de-influencers compared to traditional influencers. This research contributes to the literature by addressing the underexplored phenomenon of de-influencers and highlights their role in promoting sustainable consumer behavior, offering valuable implications for brands and marketers in the evolving landscape of social media.